PENGARUH PENGELOLAAN KEUANGAN TERHADAP KEHARMONISAN RUMAH TANGGA - Ranti Nurdiansari (Nusa Putra University, 2020)
This research aims to determine the effect of household financial management on household harmony. As for the background of this writing due to the increasing number of divorces that occur especially in sukabumi where one of the causes is economic factor. In a family there are many problems that occur these problems occur due to several factors one of which is financial factor.problems that occur due to financial can be caused by excess or lack of ability to manage finances so that expenses exceed income.in collecting data researcherused qualitative methods that emphazise the depth of data obtained by researcher with interviewing techniques using snowball sampling.the result of this research is that the ability in financial management will affect the welfare and harmony of the family.